Effect of Ankle Range of Motion Exercises Combined with Warm Water Foot Soaking on Ankle–Brachial Index in Patients with Type 2 Diabetes Mellitus - Diana, Putu Septa Ayu; Sari, Nova Nurwinda; Herlina, Herlina (Genius Journal, 2026)
Introduction: Diabetes mellitus has attracted global attention due to the increasing prevalence of cases and the potential complications it can cause, such as microangiopathy and macroangiopathy. One non-pharmacological intervention that can be applied to improve peripheral circulation is the combination of ankle range of motion (ROM) exercises and warm water foot soaking. Objective: This study aimed to determine the effect of the combined ankle ROM exercises and warm water foot soaking on Ankle Brachial Index (ABI) values in patients with Type 2 Diabetes Mellitus at Kedaton Public Health Center, Bandar Lampung, in 2025. Method: This study employed a quantitative approach with a pre-experimental design using a one-group pretest and posttest without control. A total of 30 respondents were selected using purposive sampling techniques. Data analysis included descriptive statistical analysis, a normality test using Shapiro Wilk, and a non-parametric test using the Wilcoxon Signed Rank Test. Result The results showed that the mean ABI value before the intervention was 0.0093 ± 0.04265, while after the intervention the mean ABI value improved to 0.0012 ± 0.03038. The Wilcoxon test revealed a p-value of 0.025, indicating a statistically significant difference between ABI values before and after the intervention. Conclusion: It can be concluded that the combination of ankle range of motion (ROM) exercises and warm water foot soaking has a significant effect on improving ABI values in patients with Type 2 Diabetes Mellitus, and therefore can be applied as a non-pharmacological nursing intervention to enhance peripheral blood circulation.